How did the youth’s demand for cigarette products respond to the Sin Tax Reform Act of 2012? - Nieva, Francis Ignatius L. (Animo Repository, 2021)
The excise tax on tobacco products in the Philippines has been historically low making the product very accessible even for the youth. In 2012, a Sin Tax Reform Law was passed which increased the excise tax on tobacco products by almost five times its previous value. This price increase is projected to reduce alchohol and tobacco products consumption for all demographic classifications, especially the youth. This study estimated the price elasticity of cigarette demand of the Filipino youth using regression analyses on the pooled Global Youth Tobacco Survey conducted in the Philippines for the years 2004 and 2015. Price elasticity of participation and conditional demand was found to be -0.939 and 0.574 respectively, which corresponds to the total price elasticity of demand of -0.356. The results imply that a 10% increase in price results in a total reduction of cigarette demand by 3.56 %. Findings of the study reveal that stricter compliance with youth access restrictions has to be observed to decrease cigarette consumption